Analysing the impact of entrepreneurship education on early-stage entrepreneurship: Focusing on the transitional countries of Central and Eastern Europe - Judit Csákné Filep; Gigi Timár; Áron Szennay (Administrative Sciences, 2025)
Entrepreneurship is deeply rooted in tradition and culture in many countries; however, transitional market economies in Central and Eastern Europe (CEE) underwent 40-45 years of socialism, which disrupted these traditions by collectivising private property. Education is recognised as a key tool for regional development and restoring entrepreneurial knowledge and skills, potentially enhancing entrepreneurial intentions within society. This paper investigates the impact of entrepreneurial education on entrepreneurial activity in transitional CEE countries. Pearson's correlation analysis was conducted using a combined national-level dataset from the Annual Population Survey (APS) and the National Expert Survey of the Global Entrepreneurship Monitor (GEM) spanning 2021-2023. Results reveal inconsistent findings across the years. In 2021 and 2022, there was a significant moderate correlation between total early-stage entrepreneurial activity (TEA) and an indicator of entrepreneurial education at primary and secondary levels in CEE countries. In contrast, no such relationship was observed in other regions. In 2023, however, no significant correlations were identified for any country group. These results highlight the temporal variability of education's influence on entrepreneurship in transitional economies.
Keywords: 350; Central and Eastern Europe; entrepreneurship; entrepreneurship education; Global Entrepreneurship Monitor; transitional countries